STORYTELLING METHOD: APPLICATION FOR CHILDREN WITH SPEECH DELAY DISORDER - Mahriza, Rita; Veryawan; Tursina, Ade; Damanik, Siti Anggi (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2024)
Speech delay is a condition where a child's speech development does not match the developmental stages at his age. This research aims to determine the application of the storytelling method for children with speech delay disorders and to find the factors that cause children with speech delay disorders at Al Mubarak Kindergarten, Langsa City. The method used in this research is a qualitative approach. This data was obtained through in-depth interviews with 1 teacher and 2 students who experienced speech delay at Al Mubarak Kindergarten. Meanwhile, secondary data is obtained from books, scientific works and other documents to answer all the problems in this thesis. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The research results show that the application of the storytelling method in Al Mubarak Kindergarten can be said to be very good for children with speech delay disorders. Because with the storytelling method, children feel interested in learning and understand what they are learning based on the stories told by their teacher so that children become active in everything. Here they are trained to dare to express opinions, answer questions and tell whatever they know without any restrictions. It can be seen from the learning progress of students that initially they did not want or were not confident to interact, communicate with their classmates and teachers. After conducting research, they have the courage to express their opinions or talk to friends and teachers in their language, and they also have the courage to play together. The factor that causes speech delay disorders is that children are often allowed to play with cellphones and watch television, without being accompanied by questions and answers. The conclusion is that the storytelling method applied by Kindergarten Al Mubarak for students, especially children with speech delay disorders, is working well.